Endogenous non-retroviral RNA virus elements evidence a novel type of antiviral immunity. (3rd May 2016) - Honda, Tomoyuki; Tomonaga, Keizo
ABSTRACT: Vertebrate genomes contain many virus-related sequences derived from both retroviruses and non-retroviral RNA and DNA viruses. Such non-retroviral RNA sequences are possibly produced by reverse-transcription and integration of viral mRNAs of ancient RNA viruses using retrotransposon machineries. We refer to this process as transcript reversion. During an ancient bornavirus infection, transcript reversion may have left bornavirus-related sequences, known as endogenous bornavirus-like nucleoproteins (EBLNs), in the genome. We have recently demonstrated that all Homo sapiens EBLNs are expressed in at least one tissue. Because species with EBLNs appear relatively protected against infection by a current bornavirus, Borna disease virus, it is speculated that EBLNs play some roles in antiviral immunity, as seen with some endogenous retroviruses. EBLNs can function as dominant negative forms of viral proteins, small RNAs targeting viral sequences, or DNA or RNA elements modulating the gene expression. Growing evidence reveals that various RNA viruses are reverse-transcribed and integrated into the genome of infected cells, suggesting transcript reversion generally occurs during ongoing infection. Considering this, transcript reversion-mediated interference with related viruses may be a novel type of antiviral immunity in vertebrates. Understanding the biological significance of transcript reversion will provide novel insights into host defenses against viral infections.